Cancer Immunotherapy at the Crossroads How Tumors Evade Immunity and What Can Be Done - Finke, James H; Ed. Bukowski, Ronald M; Ed (Current clinical oncology (Totowa, N.J.), 2004)
The growing evidence that tumors can evade the immune system through a variety of mechanisms makes understanding these processes critical to implementing new and more effective forms of immunotherapy. In Cancer Immunotherapy at the Crossroads: How Tumors Evade Immunity and What Can Be Done, leading investigators and clinicians detail the different mechanisms used by tumors to escape and impair the immune system and then spell out possible clinical strategies to prevent or reverse tumor-induced immune dysfunction. The authors review the mechanisms of immune dysfunction and evasion mechanisms in histologically diverse human tumors, focusing on tumor-induced molecular defects in T cells and antigen-presenting cells (dendritic cells and tumors) that may serve as biomarkers for patient prognosis. They discuss the means by which immune functions may be protected or restored in order to more effectively support the process of tumor rejection in situ. Cutting-edge techniques with the capacity to monitor the strength and quality of patients' immune responses using immunocytometry, MHC-peptide tetramers combined with apoptosis assay, ELISPOT assay, and detection of MHC-TAA peptide complexes on tumor cells are also outlined. State-of-the-art and insightful, Cancer Immunotherapy at the Crossroads: How Tumors Evade Immunity and What Can Be Done illuminates the possibilities for developing effective immunotherapies that can block the mechanisms by which tumors evade the immune system in different histologic types of tumors.